Forgiveness of the Prophet (peace and blessings be upon him) in the year of conquest – A historical and analytical study – - Amjad Saleh, Omar (Journal of College of Education, 2019)
This research deals with forgiveness of the Prophet (peace and blessings be upon him) in the year of conquest (Makka) and the desired and wanted purposes of it, and absolutely there is no doubt that the Prophet (peace and blessings be upon him) was a complete and a great model of humanity and mercy when opening Makka in the 8th year of Hijra, where the Prophet (peace and blessings be upon him) had issued a generous and great forgiveness for Makkanas although he and his companions suffered too much from Makkans and standing against him and the Islamic preaching, he forgave them to show us the most wonderful states of forgiveness. The forgiveness came in two ways: a general amnesty for all the people of Mecca, with the exclusion of a group of men and women for many reasons, including their adult hostility and hatred of Islam and Muslims The aim of this exception is to achieve the original firmness of the Prophet (peace and blessings be upon him) on the side of forgiveness in the beautiful leadership of the nation and to represent an alarm bell to review the soul and repentance from the above and return to the right path. As for the second way, it came as a special forgiveness with special intercessions, including all those who were excluded from the general amnesty after the appearance of repentance. The Prophet (peace and blessings be upon him) left them with the option of entering Islam and giving them time so that faith could be established in the hearts, with this act the Prophet (peace and blessings be upon him) made a great future for the special forgiveness for these persons in serving Islam and Muslims and achieving what the Prophet (peace and blessings be upon him) forecasted about these results of forgiveness.